2010
DOI: 10.1017/s0022112009992928
|View full text |Cite
|
Sign up to set email alerts
|

Inertial effects on the rheology of a dilute emulsion

Abstract: The behaviour of an isolated nearly spherical drop in an ambient linear flow is examined analytically at small but finite Reynolds numbers, and thereby the first effects of inertia on the bulk stress in a dilute emulsion of neutrally buoyant drops are calculated. The Reynolds numbers, Re = a2ρ/μ and $\hat{\Rey} \,{=}\, \dot{\gamma}a^2\rho/\hat{\mu}$, are the relevant dimensionless measures of inertia in the continuous and disperse(drop) phases, respectively. Here, a is the drop radius, is the shear rate, ρ is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…To validate the model, we apply it to the case of viscous droplets and Navier-slip spheres. The results correct and extend several prior results for constitutive equations of rigid spheres (Einstein 1906(Einstein , 1911Prosperetti 2004;Prosperetti et al 2006;Jin et al 2018;Zhou & Prosperetti 2020) and viscous droplets (Taylor 1932;Raja, Subramanian & Koch 2010), and are shown to be consistent with experimental observations. The study is concluded with a discussion of results and future prospects.…”
Section: Introductionsupporting
confidence: 89%
“…To validate the model, we apply it to the case of viscous droplets and Navier-slip spheres. The results correct and extend several prior results for constitutive equations of rigid spheres (Einstein 1906(Einstein , 1911Prosperetti 2004;Prosperetti et al 2006;Jin et al 2018;Zhou & Prosperetti 2020) and viscous droplets (Taylor 1932;Raja, Subramanian & Koch 2010), and are shown to be consistent with experimental observations. The study is concluded with a discussion of results and future prospects.…”
Section: Introductionsupporting
confidence: 89%
“…Further, unlike polymeric solutions, the normal stress differences for many of these systems are comparable in magnitude. Restricting ourselves to cases where analytical expressions for the normal stress differences are available: examples of such fluids include non-dilute suspensions of Brownian spherical particles (Brady & Vicic 1995), dilute suspensions of Brownian spheroids (Brenner & Condiff 1974), and dilute emulsions of surfactant-free (Raja, Subramanian & Koch 2010), surfactant-covered (Vlahovska, Blawzdziewicz & Loewenberg 2002) spherical drops and vesicles (Vlahovska & Garica 2007). Consideration of these examples below shows that varies over a significantly wider range when compared to polymer solutions alone.…”
Section: Viscoelastic Torque In Other Second-order Fluidsmentioning
confidence: 99%
“…For a dilute emulsion of surfactant-free spherical drops, the normal stress differences are O(µγ Caφ), where Ca = µγ a/Γ , Γ being the interfacial tension coefficient, plays the role of De. The microstructural anisotropy is associated with drop deformation, and the ratio of normal stress differences is now a function of the viscosity ratio (Schowalter, Chaffey & Brenner 1968;Raja et al 2010), being given by:…”
Section: Viscoelastic Torque In Other Second-order Fluidsmentioning
confidence: 99%
“…This pioneering work by Einstein in the dilute limit of solid particle suspensions has been extended to describe higher order concentration effects and/or droplet particles with finite internal viscosity (Taylor 1932(Taylor , 1934Batchelor 1970;Happel and Brenner 1983). However, even for dilute suspensions, there are higher order effects that give rise to normal stress contributions (Schowalter, Chaffey & Brenner 1968;Frankel & Acrivos 1970;Raja, Subramanian & Koch 2010), which therefore cannot be described by a modified viscosity corresponding to a generalized Newtonian model. Moreover, for suspensions of deformable liquid particles, i.e.…”
Section: Introductionmentioning
confidence: 99%